Titania‐based sol–gel coatings with Ag, Ca‐P applied on titanium substrate developed for implantation. Issue 1 (16th June 2021) - Švagrová, Kristýna; Horkavcová, Diana; Jablonská, Eva; Helebrant, Aleš
Abstract: This research work is focused on the investigation of newly developed titania sol–gel coatings containing silver, calcium and phosphate with appropriate abilities to be implanted into the human body. These abilities include adhesion, bioactivity, antibacterial property and cytocompatibility of prepared coatings. Four types of coatings were applied on a titanium substrate by dip‐coating technique under different conditions (TCP1, TCP2, TCPA1 and TCPA2). Surfaces of coatings after the firing without silver featured different distribution of circular areas containing Ca. The coatings TCPA1 and TCPA2 were made up of unhomogeneously situated silver. Adhesion of the coatings to the substrates was measured by a tape test. All types of the coatings demonstrated very good adhesion. Isolated cracks that appeared during the firing did not have a negative influence on the adhesion properties. Bioactivity of the coatings was tested in vitro using a simulated body fluid. Three of the four types demonstrated bioactive properties (TCP1, TCP2 and TCPA2), that is, precipitation of crystalline hydroxyapatite as was confirmed by X‐ray diffraction. The antibacterial effect (against Escherichia coli and Staphylococcus epidermidis ) and cytotoxicity (toward L929 and U‐2 OS cell lines, direct and indirect test) were then tested. All the coatings demonstrated very good antibacterial effect against both bacteria after 4‐ and 24‐hr interaction. All the coating types were evaluated as cytocompatible in the indirect test. Cells were able to grow even directly on the coatings.